INSTRUMENTAL KNOWLEDGE IN THE IMPLEMENTATION OF SOCIAL FUNCTIONS’ EXPERTISE - Скиба, І. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with the study of specificity of instrumental knowledge by the implementation of social functions’ expertise.